A miniature coupled‐line‐based 3‐dB directional coupler using GaAs PHEMT process. Issue 1 (4th August 2015) - Chen, Chih‐Chiang; Sim, Chow‐Yen‐Desmond; Ho, Sao‐An
ABSTRACT: A novel complementary‐conducting‐strip (CCS) coupled‐line (CL) design is proposed to achieve compact size by applying two‐dimensional layout and standard gallium‐arsenide (GaAs) thin‐film technology. To obtain high coupling and satisfy the design rules of GaAs process, mixed‐couple mechanism with edge and broadside coupling are also used. A CCS CL‐based Ka‐band 3‐dB directional coupler is fabricated using WIN 0.15‐μm GaAs pseudomorphic high electron mobility transistor technology. Experimental results show that the proposed directional coupler can cover the entire Ka‐band (26–40 GHz) with through and coupling of approximately 3.7 ± 0.25 dB, and isolation of better than 13 dB. In addition, the phase difference between the two output ports is approximately 90° ± 5°. The occupied area of the prototype (without I/O networks) is only 220 × 220 μm 2 . © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:21–26, 2016.